The last battle of the Civil War : Palmetto Ranch - Hunt, Jeffrey Wm. (Jeffrey William), 1962- (Clifton and Shirley Caldwell Texas heritage series, 2002)
More than two months after Robert E. Lee surrendered the Army of Northern Virginia on April 9, 1865, the New York Times reported a most surprising piece of news. On May 12-13, the last battle of the Civil War had been fought at the southernmost tip of Texas--resulting in a Confederate victory. Although Palmetto Ranch did nothing to change the war's outcome, it added the final irony to a conflict replete with ironies, unexpected successes, and lost opportunities. For these reasons, it has become both one of the most forgotten and most mythologized battles of the Civil War. In this book, Jeffrey Hunt draws on previously unstudied letters and court martial records to offer a full and accurate account of the battle of Palmetto Ranch. As he recreates the events of the fighting that pitted the United States' 62nd Colored Troops and the 34th Indiana Veteran Volunteer Infantry against Texas cavalry and artillery battalions commanded by Colonel John S. "Rip" Ford, Hunt lays to rest many misconceptions about the battle. In particular, he reveals that the Texans were fully aware of events in the East--and still willing to fight for Southern independence. He also demonstrates that, far from fleeing the battle in a panic as some have asserted, the African American troops played a vital role in preventing the Union defeat from becoming a rout.